2010
DOI: 10.1007/s00775-010-0715-1
|View full text |Cite
|
Sign up to set email alerts
|

Metalloporphyrin intercalation in liposome membranes: ESR study

Abstract: Liposomes characterized by membranes featuring diverse fluidity (liquid-crystalline and/or gel phase), prepared from egg yolk lecithin (EYL) and dipalmitoylphosphatidylcholine (DPPC), were doped with selected metalloporphyrins and the time-related structural and dynamic changes within the lipid double layer were investigated. Porphyrin complexes of Mg(II), Mn(III), Fe(III), Co(II), Ni(II), Cu(II), Zn(II), and the metal-free base were embedded into the particular liposome systems and tested for 350 h at 24°C us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
121
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(127 citation statements)
references
References 52 publications
6
121
0
Order By: Relevance
“…The liposomes used in our study were in the form of bubbles surrounded by a lipid bilayer membrane composed of phospholipids which surround the chain -proteins called apolipoproteins [11,12,16,17]. The fi lm of liposomes is constructed analogously to these biological membranes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The liposomes used in our study were in the form of bubbles surrounded by a lipid bilayer membrane composed of phospholipids which surround the chain -proteins called apolipoproteins [11,12,16,17]. The fi lm of liposomes is constructed analogously to these biological membranes.…”
Section: Resultsmentioning
confidence: 99%
“…2b), index (rotational correlation time) was determined. The value of this parameter depends on the fl uidity of the lipid bilayer [16][17][18]. A decrease of parameter  indicates an increased interior membrane fl uidity -increased rotational speed of the probe.…”
Section: Liposomes Preparationmentioning
confidence: 99%
“…In order to better understand the processes in the lipid bilayer, we developed a computer model of the lipid membrane and conducted an EPR experiment. The comparison of the results collected during computer simulations, with the ones obtained by EPR measurement [3], showed that several properties of lipid membranes could be associated with the structure of their surface layer. The Coulomb interactions between polar heads of the surface layer seem to be essential for the membranes in the liquid state [4].…”
Section: Introductionmentioning
confidence: 88%
“…As reported elsewhere, organometallic compounds may more or less affect the membrane's physical parameters [12][13][14]. Likewise, our previous investigations were focused mainly on structural deviations induced within the lipid arrangement by different amounts of such additives [15][16][17][18][19] including the effect of the interaction time [20,21]. On the other hand, the present work contains some novel aspects regarding the behavior of intercalated phospholipid systems, in particular the impact of the dopant's molecular structure and its static electrical charge.…”
Section: Introductionmentioning
confidence: 89%